2007
DOI: 10.1097/fjc.0b013e31811f3fd0
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Balance of Nitric Oxide/Peroxynitrite in the Dysfunctional Endothelium Can be Reversed by Statins

Abstract: Vascular endothelial dysfunction is a complex phenomenon that might be caused by a deficiency of nitric oxide (NO) and an overproduction of peroxynitrite (ONOO-). This study used a nanotechnological approach to monitor the in vitro effect of statins on the [NO]/[ONOO-] balance in normal and dysfunctional endothelial cells. NO and (ONOO-) were measured by electrochemical nanosensors in a single human umbilical vein endothelial cell (HUVEC) treated with atorvastatin or simvastatin for 24 hours in the presence or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 33 publications
2
26
0
Order By: Relevance
“…Heeba et al [100] reported that both atorvastatin and simvastatin restored the NO/peroxynitrite balance and decreased malondialdehyde (MDA), as well as wall thickness. In another study examining the effects of statins [101], statins reversed eNOS uncoupling (P \ 0.05) and increased the NO/peroxynitrite balance (P \ 0.05) in controversy to the decrease induced by oxLDL.…”
Section: Classical Agentsmentioning
confidence: 97%
“…Heeba et al [100] reported that both atorvastatin and simvastatin restored the NO/peroxynitrite balance and decreased malondialdehyde (MDA), as well as wall thickness. In another study examining the effects of statins [101], statins reversed eNOS uncoupling (P \ 0.05) and increased the NO/peroxynitrite balance (P \ 0.05) in controversy to the decrease induced by oxLDL.…”
Section: Classical Agentsmentioning
confidence: 97%
“…In addition, non-cholesterol lowering mechanisms by statins have also been attributed to inhibit NADPH oxidase-associated redox signaling (Hattori et al, 2003;Mason et al, 2004;Heeba et al, 2007). For example, statins block HMG-CoA reductase, and the synthesis of isoprenoids and isoprenylation of Rac is essential for Rac translocation to plasma membrane and its activation.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37] Depleted NO and high ONOO − production by cells resulting in a low ratio (,1.0) of maximal NO to maximal ONOO − concentrations have been used as an accurate indicator of oxidative stress leading to dysfunctional endothelium. 16,18 Therefore, we studied in situ real-time dynamic interaction of the amorphous silica nanoparticles with primary HUVECs by measuring NO and ONOO − concentrations directly using nanosensors placed 5 ± 2 µm from the plasma membrane of a single cell. We demonstrated with time resolution better than 10 microseconds that these nanoparticles rapidly stimulated NO release, followed by ONOO − production after collision with cells ( Figure 2A).…”
Section: Internalization Of Amorphous Silica Nanoparticles Into Huvecsmentioning
confidence: 99%
“…15 High ONOO − production and depleted NO availability resulting in a low ratio (,1.0) of maximal NO to maximal ONOO − concentrations ([NO]/[ONOO − ]) can be used accurately as an indicator of nitroxidative/oxidative stress and endothelial dysfunction. [16][17][18] It has been suggested that oxidative stress induces upregulation of gene expression by transcription factor activation. 19 When activated, these factors initiate the transcription of several genes involved in inflammation and coagulation.…”
Section: Introductionmentioning
confidence: 99%